Management of Sternal Wound Infection—Determinants of Length of Stay and Recurrence of Infection after Muscle Flap Coverage - Feller, Kathrin; Schipper, Lukas; Liu, Juan; Phan, Truong Quang Vu; Kroeger, Knut; Joeckel, Karl-Heinz; Lax, Hildegard (The Thoracic and Cardiovascular Surgeon, 2023)
Aim The aim of this study was to define determinants of length of hospital stay (LOS) longer than mean and recurrence of infection (ROI) after complete healing of patients with deep sternal wound infections (DSWI).Patients and Methods In this observational study, we included 303 patients (155 females and 148 males, with mean age of 68 years) treated from 2016 to 2020 at the Department of Plastic Surgery of the HELIOS Klinik Krefeld, Germany. All patients received extensive necrosectomy, repetitive negative pressure therapy periods, and final transplantation of a pectoral musculocutaneous flap. In the German diagnosis-related group (DRG)-system, the mean inpatient LOS depends on the number of surgical procedures and is longer in those with four or more surgical procedures (DRG IO2B) and shorter in those with fewer procedures (DRGs I02C and I02D). The determinants which have a significant effect on LOS longer than mean and ROI after complete healing were identified by estimating a logistic regression model. The effect of the different calculated determinants was quantified as odds ratio. To measure the discriminant ability of the model between patients, we determined a receiver operating characteristic curve. The fit of the model was quantified by comparing predicted probabilities of the model with empirical probabilities of the data. The goodness of fit was then measured by applying the Hosmer–Lemeshow test.Results Among patients in DRG IO2B (n = 246), the variable clopidogrel and therapeutic anticoagulation was the most important determinant for a longer LOS, with an odds ratio of 5.83 (95% CI = 0.83/40.80). Female sex and renal insufficiency also prolonged LOS. Applying this analysis to the patients with group DRG groups I02C and I02D (n = 57), none of these parameters were predictive. The variable immunosuppression was the most important determinant for ROI (n = 49) (OR = 4.67; 95% CI = 1.01/21.52). Body mass index also played a role, but with a much smaller influence.Conclusion There are specific risk factors for LOS longer than mean and ROI in patients with DSWI that can be identified on admission. Addressing these risk factors, if possible, could reduce the rate of patients with LOS longer than mean and ROI.
Keywords: deep sternal wound infections; clopidogrel; anticoagulation; immunosuppression; body mass index